2014
DOI: 10.1017/s1041610214001434
|View full text |Cite
|
Sign up to set email alerts
|

A new measure of fear of falling: psychometric properties of the fear of falling questionnaire revised (FFQ-R)

Abstract: Background Although fear of falling is prevalent among older adults recovering from hip fracture, current instruments are inadequate due to focus on specific situations and measurement of self-efficacy rather than fear. Methods The authors revised and tested a form of the Fear of Falling Questionnaire with three groups of older adults: 405 recovering from hip fracture, 89 healthy community-dwelling, and 42 with severe fear of falling. Test-retest reliability was evaluated in a subsample of 16 hip fracture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…The FFQ also displays good criterion validity by differentiating those who endorse FoF from those who do not. A recent analysis of this measure using this dataset confirmed its utility . The FFQ is completed using a 4‐point scale ranging from strongly disagree to strongly agree for each question.…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…The FFQ also displays good criterion validity by differentiating those who endorse FoF from those who do not. A recent analysis of this measure using this dataset confirmed its utility . The FFQ is completed using a 4‐point scale ranging from strongly disagree to strongly agree for each question.…”
Section: Methodsmentioning
confidence: 70%
“…Despite other research showing that approximately 4% of elderly adults hospitalized for a fall‐related injury develop PTSD, the current study found that only 3% (n = 11) had probable fPTSD according to the PCL‐S screening measure and that, of these, none met criteria for full diagnosable PTSD using the CAPS. Given the lack of fPTSD and that, in many trauma‐exposed populations, pPTSD is more prevalent than fPTSD and is also associated with significant psychiatric impairment, it was decided to focus on individuals with pPTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another thing to consider about fear of falling is that it is multi-dimensional and strongly correlated to "the perceived threat of falling, perceived risk of falling, concern about the consequences of falls, and fall-related self-efficacy" (Liu, 2015, p. 1). While the FES is considered to be a reliable and valid assessment to use to measure fear of falling, it only captures the perceived self-efficacy dimension of fear of falling in an individual (Bower et at., 2015).…”
Section: Chapter 5: Discussionmentioning
confidence: 99%
“…The reverse is also true in that there are age-specific and fear related situations that are insufficiently captured using existing instruments. A prime example is fear of falling, an instrument for which is tested for the first time in a large sample of elderly persons recovering from hip fracture in the current issue (Bower et al, 2015). This issue also contains a review of psychological factors associated with falls-related psychological concerns in community-dwelling older people (by Hughes and colleagues), which further explicates this important topic with respect to late-life anxiety.…”
mentioning
confidence: 99%